2014
DOI: 10.1192/bjp.bp.113.132308
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in cortical and extrastriatal subcortical dopamine function in schizophrenia: systematic review and meta-analysis of imaging studies

Abstract: There is a relative paucity of direct evidence for cortical dopaminergic alterations in schizophrenia, and findings are inconclusive. This is surprising given the wide influence of the hypothesis. Large, well-controlled studies in drug-naive patients are warranted to definitively test this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 84 publications
2
70
0
Order By: Relevance
“…Deviations in prefrontal DAergic activity may perhaps not be expected based on inconclusive findings in the existing literature on DA in psychosis (Kambeitz et al, 2014), although recent work seems to suggest blunted amphetamine-induced DAergic activity in SZ as measured with FLB457 (Slifstein et al, 2015). Again, replication samples and especially the use of high-affinity D2/3 tracers may provide insight into altered stress-induced cortical DAergic activity associated with psychosis (vulnerability).…”
Section: The Dysregulated Stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Deviations in prefrontal DAergic activity may perhaps not be expected based on inconclusive findings in the existing literature on DA in psychosis (Kambeitz et al, 2014), although recent work seems to suggest blunted amphetamine-induced DAergic activity in SZ as measured with FLB457 (Slifstein et al, 2015). Again, replication samples and especially the use of high-affinity D2/3 tracers may provide insight into altered stress-induced cortical DAergic activity associated with psychosis (vulnerability).…”
Section: The Dysregulated Stress Responsementioning
confidence: 99%
“…DA is a catecholamine that is functionally involved in cognition, movement, reward motivation and salience attribution -the assignment of importance to a stimulus (Arnsten et al, 1994;Berridge and Robinson, 1998;Goldman-Rakic, 1998). Most importantly however, changes in brain DA function have been related to stress-related psychopathological conditions such as substance abuse (Robinson and Berridge, 1993), post-traumatic stress disorder (De Bellis et al, 1999;Glover et al, 2003;Hamner and Diamond, 1993;Lemieux and Coe, 1995;Spivak et al, 1999;Yehuda et al, 1992) and psychosis (Howes and Kapur, 2009;Kambeitz et al, 2014). Especially the latter disorder has consistently been associated with increased striatal DA synthesis capacity and release (Fusar-Poli and Meyer-Lindenberg, 2013;Howes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Postiron emission tomography (PET) studies with displaceable DA D2/D3 receptor (D2/D3R) radioligands show that low striatal D2/D3R availability may be associated with impulsivity (Clark et al, 2012), addiction to alcohol (Volkow et al, 1996; Martinez et al, 2005), substance abuse (Volkow et al, 1990; Volkow et al, 2001; Martinez et al, 2004; Fehr et al, 2008), and obesity (Wang et al, 2001; Haltia et al, 2007; de Weijer et al, 2011) whereas high D2/D3R availability has been associated with risk for schizophrenia (Laruelle, 1998), although this finding has not been replicated (Howes et al, 2012; Kambeitz et al, 2014). Similarly, the A1 (T) allele of the single nucleotide polymorphism (SNP) TaqIA (rs1800497), located in the ankyrin repeat and kinase domain containing 1 ( ANKK1 ) 10 kb downstream from the DA D2 receptor ( DRD2 ) gene (Grandy et al, 1989), is associated with addictive behavior including gambling (Comings et al, 1996), substance abuse (Noble et al, 1993; Persico et al, 1996; Lawford et al, 2000; Chen et al, 2004; Messas et al, 2005), and binge eating (Davis et al, 2012) and with obesity (Noble et al, 1994; Spitz MR, 2000; Thomas et al, 2001; Stice et al, 2008; Duran-Gonzalez et al, 2011) while the A2 (C) allele is associated with risk for schizophrenia (Parsons et al, 2007; Dubertret et al, 2010; Arab and Elhawary, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…13,14 In patients with schizophrenia, the presynaptic DA marker [ 18 F]DOPA has been shown to be elevated, whereas studies on postsynaptic DA receptors have produced discrepant results. 15,16 Striatal D 2/3 dopamine receptor availability has been found to be reduced in most substance use disorders 17,18 but negative findings have also been reported. [19][20][21] Various studies of the serotonin 5-HT 1A receptor in depression have shown decreased, increased or unaltered levels.…”
Section: Introductionmentioning
confidence: 99%